2011
DOI: 10.1152/ajpheart.00360.2010
|View full text |Cite
|
Sign up to set email alerts
|

Aging attenuates the vasodilator response to relaxin

Abstract: Relaxin, an insulin-like growth factor peptide, increases endothelium-dependent vasodilation and vascular compliance and decreases myogenic reactivity. These vascular effects significantly contribute to the physiological circulatory adaptations in pregnancy, particularly in the mesentery and kidney. Aging predisposes to vascular maladaptation and gestational hypertensive disease. We hypothesized that mild aging reduces the vascular responses to relaxin. In 20 young (10-12 wk) and 20 middle-aged (40-46 wk) fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 30 publications
3
43
1
Order By: Relevance
“…Previous reports have indicated that relaxin simulates NOmediated responses in multiple vascular and non-vascular tissues , Novak et al 2002, Failli et al 2005, McGuane et al 2011, van Drongelen 2011. Our data show that TA and Branch arterioles dilate to the same extent relaxin, once the maximum size of the vessels is taken into account; however, MI arterioles do not respond directly to relaxin.…”
Section: Different Microvascular Responses To Relaxinsupporting
confidence: 49%
“…Previous reports have indicated that relaxin simulates NOmediated responses in multiple vascular and non-vascular tissues , Novak et al 2002, Failli et al 2005, McGuane et al 2011, van Drongelen 2011. Our data show that TA and Branch arterioles dilate to the same extent relaxin, once the maximum size of the vessels is taken into account; however, MI arterioles do not respond directly to relaxin.…”
Section: Different Microvascular Responses To Relaxinsupporting
confidence: 49%
“…In association with renal vasodilation, myogenic constriction of small renal arteries isolated from the relaxin-treated rats was inhibited, thus mimicking the inhibited myogenic constriction observed in small renal arteries from midterm pregnant rats [17,18]. When relaxin was administered to rats, flow-mediated vasodilation of isolated mesenteric arterioles was increased, analogous to midterm pregnancy [19,20]. However, this effect of relaxin was not observed in aged rats [20].…”
Section: Chronically Instrumented Conscious Ratsmentioning
confidence: 83%
“…When relaxin was administered to rats, flow-mediated vasodilation of isolated mesenteric arterioles was increased, analogous to midterm pregnancy [19,20]. However, this effect of relaxin was not observed in aged rats [20]. Analogous to both midterm and late pregnancy [21][22][23], the renal vasoconstrictor response to an acute intravenous infusion of angiotensin II was attenuated in nonpregnant rats that were chronically administered relaxin [14].…”
Section: Chronically Instrumented Conscious Ratsmentioning
confidence: 99%
“…Vasorelaxation was attenuated with the advance of age [153]. Correspondingly, activity of BK Ca channels in VSMCs significantly decreased during aging [154,155].…”
Section: Bkca Channel Function In Physiological Conditionsmentioning
confidence: 99%